Morbidity profile of migrant workers attending health camps in Bangalore urban during the Covid-19 pandemic - Soumya Chippagiri; Sakthi Arasu; Naveen Ramesh; Ramakrishna Goud; Bobby Joseph (International Journal of Occupational Safety and Health, 2023)
Introduction: Global pandemic of COVID-19 resulted in a nationwide lockdown which affected the migrants in terms of healthcare service accessibility. This led to an increase in the prevalence of various morbidity. The objective of this study was to assess the morbidity profile of camp attendees in Bangalore urban conducted during the lockdown period of the COVID-19 pandemic.